Understanding the quality use of research evidence in education what it means to use research well - Rickinson, Mark; Walsh, Lucas; Gleeson, Joanne; Cutler, Blake; Cirkony, Connie; Salisbury, Mandy (New York, NY Routledge, 2024)
This book focuses in on the question of how to understand quality use of research evidence in education, or what it means to use research evidence well. Internationally there are widespread efforts to increase the use of research evidence within educational policy and practice. Such efforts raise important questions about how we understand not just the quality of evidence, but also the quality of its use. To date, there has been wide-ranging debate about the former, but very little dialogue about the latter. Based on a five-year study with schools and school systems in Australia, this book sheds new light on: why clarity about quality of use is critical to educational improvement; how quality use of research evidence can be framed in education; what using research well involves and looks like in practice; what quality research use means for individuals, organisations and systems; and what aspects of using research well still need to be better understood. This book will be an invaluable resource for professionals within and beyond education who want to better understand what using research evidence well means and involves, and how it can be supported"-- Provided by publisher.
Quality use of research as a gap -- Quality use of research as an aspiration -- Quality use of research as a capacity -- Quality use of research as a culture -- Quality use of research as a practice -- Quality use of research as a system -- Conclusion - quality use of research next steps.
Keywords: Education -- Research -- Australia -- Case studies; Educational change -- Australia -- Case studies; Education and state -- Australia -- Case studies